2021
DOI: 10.1044/2020_jslhr-20-00415
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Parental Perspectives of Childhood Speech and Language Disorders Across 10 Countries: A Pilot Qualitative Study

Abstract: Purpose Although researchers have explored parental perspectives of childhood speech and language disorders, most studies have been conducted in English-speaking countries. Little is known about parental experiences across countries, where procedures of language screening and services for language disorders differ. The authors participated in the COST 1 Action network IS1406, “Enhancing Children's Oral Language Skills Across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In that case, two facts should be kept in mind: (1) as stated by Allen and Marshall (2011), the motivation of parents to participate in the intervention is an important variable: even the shortest intervention requires involvement and consistency that sometimes parents cannot ensure, and this may influence on the effectiveness of the intervention; and (2) involvement of a third person in the implementation of intervention does not mean replacement of the SPL. Parents can be good partners if they are motivated and well mentored by a speech–language therapist or specialists in the field, and they also have good knowledge of which areas of pragmatics are challenging for their child (Jensen de López et al., 2021) but this does not mean that they can completely replace a speech–language therapist. As Fey et al.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, two facts should be kept in mind: (1) as stated by Allen and Marshall (2011), the motivation of parents to participate in the intervention is an important variable: even the shortest intervention requires involvement and consistency that sometimes parents cannot ensure, and this may influence on the effectiveness of the intervention; and (2) involvement of a third person in the implementation of intervention does not mean replacement of the SPL. Parents can be good partners if they are motivated and well mentored by a speech–language therapist or specialists in the field, and they also have good knowledge of which areas of pragmatics are challenging for their child (Jensen de López et al., 2021) but this does not mean that they can completely replace a speech–language therapist. As Fey et al.…”
Section: Discussionmentioning
confidence: 99%
“…The link between beliefs and behaviors is a longstanding research area in social science (e.g., Bornstein et al, 2017). Prior research has shown that adults make assumptions about children’s cognition and adjust their behavior based on these assumptions (e.g., linguistic tuning hypothesis; Jensen de López et al, 2021 ; MacPhee, 1983 ; Sigel & McGillicuddy-De Lisi, 2002 ; Snow, 1972 ; Yurovsky et al, 2016 ). Their beliefs and behaviors surrounding children’s language development can even influence children’s long-term language outcomes (Bojczyk et al, 2016 ; Donahue et al, 1997 ; Del Vecchio et al, 2014 ; Hunt & Paraskevopoulos, 1980 ; Jimerson & Bond, 2001 ; Winstanley et al, 2014 ; Zippert & Ramani, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, themes were refined, and transcripts were re‐read to ensure no important points were missed. The interviews and analysis were conducted in Danish, and, in accordance with Jensen de López et al (2021), extracts of the data were not translated to English before the final themes were refined. This was done to respect the original meaning of each interview in the process of analysis.…”
Section: Methodsmentioning
confidence: 99%